Effects of Obesity on Musculoskeletal Health - Mahalle, Pranay Santosh Rao (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Obesity is a growing global health concern with significant impacts on various physiological systems, particularly the musculoskeletal system. Excess body weight and altered fat distribution are known to influence bone density, joint health, muscle function, and overall quality of life. This abstract provides a detailed overview of the effects of obesity on musculoskeletal health, summarizing recent research findings and highlighting the multifaceted nature of these impacts. Obesity impacts bone health through increased mechanical loading and changes in bone structure. While higher body weight can increase bone density, it does not necessarily improve bone quality. Advanced imaging has shown that obesity-related changes such as increased marrow adiposity and altered trabecular structure contribute to a higher risk of fractures and potentially accelerate bone degeneration. Resistance training has been shown to effectively counteract muscle atrophy and improve muscle function in obese individuals. Fat distribution also plays a role, with abdominal fat having a more detrimental effect on muscle health compared to peripheral fat. Aim: The study aims to synthesize current research on how obesity affects musculoskeletal health, focusing on bone health, joint stress, muscle function, and psychosocial outcomes. The goal is to elucidate the mechanisms through which obesity contributes to musculoskeletal disorders and to underscore the importance of comprehensive management strategies. Material and Method: This cross-sectional observational study was conducted in Department of Orthopedics, Tertiary Care Hospital. Participants were informed about the study and provided verbal informed consent. All patients enrolled in the obesity and metabolic diseases program were included in the study. Each participant completed a Clinical Questionnaire to describe their pain across various musculoskeletal locations, specifying the anatomical areas and the intensity of pain experienced over the past three months. The study population was characterized based on personal details (gender, age, and body mass index) as well as their reported pain. Participants used a numeric rating scale from 0 to 10 to assess pain intensity in seven anatomical regions: hand & wrist, shoulder, lumbar region, hip, knee, ankle, and foot. Results: The data reveals that, out of the 100 participants, 80 are female, accounting for 73.4% of the sample, indicating a predominance of females in this study. The mean age of the participants is 38.12 years, with a standard deviation of 7.49 years, reflecting a broad age range within the sample. The average BMI is 31.22 kg/m2 with a standard deviation of 2.15, suggesting that most participants’ BMI values are clustered around the mean. The high percentages of participants classified as overweight (60%) and obese (40%) point to a significant proportion of the group being at risk for health problems related to excessive body weight. Correlations with shoulder, knee, and ankle pain are moderate, whereas correlations with hand & wrist, lumbar region, hip, and foot pain are weak or negligible. Overall, most correlations are very weak, though there is a slightly higher correlation noted for foot pain measurements.